Plant nutrient supply from nine agroforestry tree species to wheat (Triticum aestivum) analysed by vector diagnosis - Anthofer, J.; Hanson, Jean; Jutzi, S.C. (Wiley, 1997)
Six-week-old wheat seedlings (Triticum aestivum) grown in pots with an alfisol soil with vertic properties and mulched at a rate equivalent to 10 t ha−1 with leaf prunings of Grevillea robusta, Erythrina abyssinica, Gliricidia sepium, Albizia schimperiana. Acacia nilotica. Acacia polyacantha, Leucaena leucocephala, Leucaena pallida and Entada abyssinica were used to diagnose nutrient contributions by these tree species. A control treatment of 20kg P+ 30kg N ha−1 was chosen as the reference treatment for the vector analysis applied to the mulch effects. Nitrogen was found to be the most important nutrient in seedlings mulched with L. pallida, L. leucocephala, Erythrina abyssinica and to a lesser extent A. schimperiana. Other nutrients of these mulches were also in the deficiency zone but with shorter vectors and therefore with lower impact. Since all these mulches showed increased values for shoot dry weight, nutrient concentration and nutrient uptake they have still reserves for further plant growth and appear therefore to be good mulch sources for annual crops. In contrast, wheat seedlings treated with A. polyacantha and Entada abyssinica had at least some vectors in the toxic zone due to an excess of nutrients while Grevillea treated plants showed a typical toxicity response with large vectors for all nutrients in between the toxic and the antagonistic zone. Allelopathic compounds might also have been involved.